Evaluation of the Laguerre–Gaussian mode purity produced by three-dimensional-printed microwave spiral phase plates. Issue 7 (22nd July 2020) - Isakov, D.; Wu, Y.; Allen, B.; Grant, P. S.; Stevens, C. J.; Gibbons, G. J.
Abstract : Computer-aided design software and additive manufacturing provide flexibility for the direct fabrication of multi-material devices. This design and fabrication versatility has been investigated for the manufacture of dielectric spiral phase plates (SPP) that generate electromagnetic waves with helical wavefronts. Three types of SPPs designed to produce an orbital angular momentum (OAM) mode number l = |1| were additively manufactured using material extrusion and polyjet fabrication methods. The OAM mode characteristics of the transformed helical microwaves as a function of the SPP geometrical features were investigated experimentally in the 12–18 GHz frequency range. The SPPs were further combined with an additively manufactured dielectric lens that provided a marked improvement in OAM mode purity. Finally, multiplexing and de-multiplexing of two OAM modes were demonstrated successfully using an optimum SPP geometry and arrangement.